Isotopic data from the Pomarinho enclave swarm (SW Iberian Chain) - Moita, P. (2011)
Mafic microgranular enclaves are a common feature of calc-alkaline granitoids (e.g. tonalites and granodiorites) in active continental margins and collisional orogens. They correspond to dark-coloured globules that, although widespread throughout the host rock, usually constitute only a small proportion of the whole volume of the intrusion. When the enclaves occur strongly concentrated in a restricted area, they form an enclave swarm (e.g. Tobish et al. 1997). At Pomarinho, the Granialpa quarry is a privileged exposure of a cluster of dark igneous enclaves that has been targeted for geochemical and geophysical studies (GeoRadar and AMS). The Pomarinho swarm is located in the SW edge of Évora granitoid (Carvalhosa, 1983), in the Portuguese sector of the Ossa-Morena Zone (Iberian Variscides). The enclaves have tonalitic and granodioritic compositions, whereas the host correspond to a very homogeneous light-coloured granodiorite. Preliminary geochemical information, based on major and trace elements (Moita et al., 2011), suggests that the enclaves and the host rock are probably derived from co-genetic magmas. Rb-Sr isotope data now obtained in four enclaves and three host-rock samples yield an isochron corresponding to 335±14Ma (MSWD=0.96), which fits into the spectrum of ages of the Variscan granitoids in the region. Additionally, the homogeneity of both 87Sr/86Sr335 (0.704758 to 0.705133) and εNd335 (-0.10 to 1.13) values corroborates the hypothesis of derivation of the enclaves and the host granodiorite from a common primitive melt through magmatic differentiation. Low 87Sr/86Sr335 and high εNd335 values suggest that ultimately the parental melt is related to a mantle source, with no or only small contribution of metasedimentary crustal materials.